Gaba metabolism in Venezuelan equine encephalomyelitis virus infection. Preliminary communication - Bonilla, Ernesto; Ryder, Slavia; Estevez, Jesús (Investigación Clínica, 2013)
Mice infected with Venezuelan equine encephalomyelitis virus showed a significant decrease in GABA content of cerebral hemispheres. Activity of the enzyme which synthesizes GABA, glutamic acid decarboxylase, is also reduced in whole cerebral hemispheres, caudate nucleus, and frontal cortex of infected animals, as compared to values obtained from the same regions of control mice.